Rethinking punitive damages - Katsampouka, E (2021)
Punitive damages are a species of non-compensatory damages. Their principal purpose is to punish the defendant for his or her wrongful conduct. This thesis is the first monograph-length treatment dedicated exclusively to this contentious remedy. Through empirical, historical and doctrinal analysis, it illuminates the practical operation of the remedy and assesses its appropriateness. The thesis is divided into three parts. Part I explores the relevant law and its normative underpinnings. Part II provides an empirical survey of nearly 600 decisions on punitive damages delivered by courts at first instance and on appeal between 1964 and 2020 in all parts of the UK (with the exception of Scotland which does not recognise the remedy). The empirical analysis examines various assertions made in the case law and academic literature regarding the operation of the remedy by treating them as testable hypotheses and reveals the extent to which these assertions conform with the empirical evidence. Part III assesses the main limitations on the availability of punitive damages in English law in light of the normative basis of the remedy, its history and the empirical findings. The two limitations examined are the confinement of punitive damages awards to specific categories of case (the ‘categories test’) and to specific types of wrongs (‘cause of action restrictions’). It is argued that these restrictions are unjustified and should be abolished. The thesis concludes that the circumstances in which punitive damages are currently available should be expanded and that their availability should depend on an assessment of the defendant’s conduct rather than the case category or the formal classification of the wrong in which the claimant sues.